Challenges ahead in integrating technology & people - Sastry, A.S (ed.) ...[et. al] (Bombay, 1988)
There have been impressive technological developments during the past few years which have made tremendous impact on the society. The developmental goals can be achieved only by ensuring that the benefits of technology reach the people for their welfare. Realising the need for integrating technology and people for rapid socio-economic development, a regional convention on "INTEGRATING TECHNO LOGY AND PEOPLE: CHALLENGES AHEAD" was organised by the Hyderabad Chapter of Indian Institution of Industrial Engineering in 1985. This book contains select papers presented by eminent personalities in the convention. The role of industrial engineers in integrating technology and people is the main focus of this book. It is hoped that the book will be useful to policy makers, industrial engineers, research and training institutions, and managerial personnel involved in the task of promoting technology and integrating it with people's needs.
Keywords: Technology Social aspects